Pengaruh Literasi Keuangan dan Perilaku Keuangan Terhadap Keputusan Investasi Mahasiswa Perguruan Tinggi Swasta di Jakarta - Ayu Rizki Utami; Siti Ruhana Dara (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of financial literacy and financial behavior on investment decisions of private tertiary institutions in Jakarta. This study uses a quantitative approach through the distribution of questionnaires with samples taken as many as 105 respondents obtained using non-probability sampling techniques and purposive sampling methods. The research data were processed with SPSS, where hypothesis testing was analyzed using t test and multiple linear regression analysis. The results of this study indicate that the financial literacy variable has no significant effect on investment decisions, based on the results of the t-test which shows the t count is lower than the t table (1.962> 1.98350). Likewise, the variable of financial behavior has a significant effect on investment decisions, which is indicated by the value of t count higher than t table (3,791> 1,98350).